2012
DOI: 10.1210/en.2012-1045
|View full text |Cite
|
Sign up to set email alerts
|

Arcuate Kisspeptin/Neurokinin B/Dynorphin (KNDy) Neurons Mediate the Estrogen Suppression of Gonadotropin Secretion and Body Weight

Abstract: Estrogen withdrawal increases gonadotropin secretion and body weight, but the critical cell populations mediating these effects are not well understood. Recent studies have focused on a subpopulation of hypothalamic arcuate neurons that coexpress estrogen receptor α, neurokinin 3 receptor (NK(3)R), kisspeptin, neurokinin B, and dynorphin for the regulation of reproduction. To investigate the function of kisspeptin/neurokinin B/dynorphin (KNDy) neurons, a novel method was developed to ablate these cells using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
136
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 169 publications
(146 citation statements)
references
References 87 publications
9
136
1
Order By: Relevance
“…Although the mechanism remains to be determined, these findings are relevant to understanding thermoregulatory dysfunction in menopausal women, who tolerate heat stress better after estrogen replacement therapy (52). We have previously shown that KNDy neurons are required for the rise in LH secretion after the removal of E 2 negative feedback (11). Fig.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Although the mechanism remains to be determined, these findings are relevant to understanding thermoregulatory dysfunction in menopausal women, who tolerate heat stress better after estrogen replacement therapy (52). We have previously shown that KNDy neurons are required for the rise in LH secretion after the removal of E 2 negative feedback (11). Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Rats were also exposed to subneutral, neutral, and supraneutral T AMBIENT in an environmental chamber to determine if KNDy neuron ablation altered the ability to defend T CORE in response to environmental temperature challenges. Our previous studies have shown that KNDy neurons are required for tonic gonadotropin secretion, the rise in LH secretion after ovariectomy, and the E 2 modulation of body weight (11). Here we determine if KNDy neurons also participate in the E 2 modulation of thermoregulation.…”
mentioning
confidence: 81%
See 3 more Smart Citations